THE INFLUENCE OF PRICE PERCEPTION, SHIPPING COSTS, AND MARKETING CONTENT ON PURCHASE DECISIONS WITH TRUST AS A MODERATING VARIABLE AMONG SHOPEE MARKETPLACE USERS IN MEDAN CITY - Edward, Yusuf Ronny; Louise, William; Lie, Darwin; Guci, Dede Ansyari; Sihombing, Yeni Rafita (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2026)
This study aims to analyze the influence of price perception, shipping costs, and marketing content on purchase decisions, with trust serving as a moderating variable among Shopee marketplace users in Medan City. The rapid growth of e-commerce platforms has intensified competition, making it essential for online marketplaces to understand consumer behavior, particularly the factors that shape purchasing decisions. A quantitative method was applied using purposive sampling, involving respondents who have made purchases on Shopee. Data were obtained through structured questionnaires and analyzed using multiple linear regression combined with Moderated Regression Analysis (MRA) to examine both direct and moderating effects. The findings reveal that price perception significantly influences purchase decisions, indicating that consumers evaluate fairness, attractiveness, and value before making online purchases. Shipping costs also have a significant positive effect, demonstrating that affordable or subsidized delivery fees encourage higher purchase intention. Marketing content, including product descriptions, visuals, and digital promotions, likewise significantly affects purchasing decisions by enhancing consumer engagement and information clarity. However, trust does not moderate the relationship between these independent variables and purchase decisions, suggesting that the influence of price, shipping costs, and marketing content remains consistent regardless of trust levels. These results highlight the importance for e-commerce platforms to optimize pricing strategies, reduce delivery fees, and strengthen marketing content to drive consumer decisions.